Assessment of the impact of subgrid-scale stress models and mesh resolution on the LES of a partially-premixed swirling flame. (1st December 2020) - De Santis, Andrea; Clements, Alastair G.; Pranzitelli, Alessandro; Ingham, Derek B.; Pourkashanian, Mohamed
Abstract: Large Eddy Simulation (LES) has become an attractive option for the modelling of turbulent combustion, and a significant effort has been put into the development of suitable models for combustion at the subgrid-scale (SGS). Comparatively, little attention has been paid to the impact of SGS stress models in the simulation of complex reactive flows. In the present work, a partially-premixed case from the Sydney swirl-stabilised flames series has been investigated using LES and the Flamelet Generated Manifold (FGM) approach, employing four different SGS stress models on three numerical grids with different levels of refinement, quantified with an a priori mesh quality criterion. It was found that the use of advanced SGS models can improve the accuracy of the results significantly in both the highly turbulent region close to the burner and in the low-turbulence region further downstream. Also, a physically sound formulation for SGS stresses was found to reduce the sensitivity of the results to mesh refinement, giving acceptable results on relatively coarse grids. This can be a significant advantage in the modelling of complex geometries where there is a need to find a compromise between mesh refinement and computational costs.